Acute mitral chodae rupture in the early postcovid in heavy physical active men. Case series - Z. N. Sukmarova; Yu. V. Ovchinnikov; O. M. Larina; S. O. Lependin; O. V. Afonina; A. I. Gromov (National Electronic Information Consortium (NEICON), 2022)
The opinion that COVID-19 is a greater threat only to the elderly people has changed over the past year. Experience has been accumulated in the development of complications of varying severity in young patients who had optimal health indicators before infection. The consequences of myocarditis are most dangerous, especially in athletes and military personnel. We present a series of clinical cases of spontaneous mitral valve chordae rupture in highly trained middle-aged men in the early post-COVID period. In all cases, the infection proceeded subclinically; SARS-CoV-2 was verified only by analysis for IgM. 1-2 weeks after infection, against the background of a routine training process, patients felt pain in the heart area, which was underestimated. Patients presented for help at 2 and 10 weeks with complaints of reduced endurance and shortness of breath. Echocardiography revealed rupture of one of the chords of the anterior part of the mitral valve against the background of signs of myocarditis with the development of valvular insufficiency of the 1st degree. By the time of treatment, the pathology of other laboratory data and ECG was not observed. The control after 6 months showed in 1 patient a focus of myocardial fibrosis according to MRI, a minimal increase in NT-proBNP, a decrease in exercise tolerance, in 2 patients there was no visible fibrosis, normal NT-proBNP and complete restoration of exercise tolerance, but a decrease in local myocardial deformation according to echocardiography.